2022
DOI: 10.1093/jacamr/dlac126
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and antimicrobial resistance patterns ofEnterococcusspecies isolated from laying hens in Lusaka and Copperbelt provinces of Zambia: a call for AMR surveillance in the poultry sector

Abstract: Background The use of antimicrobials in layer poultry production for improved production, growth promotion, prophylaxis and treatment purposes has contributed to the development of antimicrobial resistance (AMR) in poultry. In Zambia, there is a paucity of information on the prevalence and AMR patterns of Enterococcus species isolated from laying hens. Objectives This study investigated the prevalence and AMR patterns of ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
2
19
2
Order By: Relevance
“…On average, E. faecium exhibited increased resistance to antimicrobials in comparison with E. faecalis . Our findings are in agreement with a recent study conducted in Zambia [ 29 ]. Our study also has some similarities with a study conducted in the Czech Republic [ 48 ], in which increased resistance of Enterococci to tetracycline, erythromycin and nitrofurantoin were observed, as well as a study from USA [ 49 ], in which Enterococci resistance to tetracycline, penicillin and ciprofloxacin was documented.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On average, E. faecium exhibited increased resistance to antimicrobials in comparison with E. faecalis . Our findings are in agreement with a recent study conducted in Zambia [ 29 ]. Our study also has some similarities with a study conducted in the Czech Republic [ 48 ], in which increased resistance of Enterococci to tetracycline, erythromycin and nitrofurantoin were observed, as well as a study from USA [ 49 ], in which Enterococci resistance to tetracycline, penicillin and ciprofloxacin was documented.…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with other studies that reported similar results in Poland [ 26 ], Malaysia [ 27 ] and Nigeria [ 28 ]. However it was lower than that reported in a similar study conducted in Zambia, where the prevalence was 88.4% in laying hens [ 29 ]. This could be due to differences in sampling methods, farms sampled and the number of farms sampled.…”
Section: Discussioncontrasting
confidence: 70%
“…To determine antimicrobial resistance genes carried by the E. coli strains isolated from the chicken, a conventional colony PCR was done as described before 16 , 17 but with modifications. Both naïve and E. coli resistant to either tetracycline or sulfonamides were tested.…”
Section: Methodsmentioning
confidence: 99%
“… 94 , 104–108 Consequently, there is evidence of antimicrobial-resistant pathogens across the human and animal sectors. 37 , 38 , 41 , 99 , 109–115 A study by Masich et al 116 revealed that about 67% of antimicrobials were inappropriately prescribed to non-critically ill adult patients admitted to the University Teaching Hospital in Lusaka, Zambia. Intriguingly, the Zambian government has put in measures to promote the appropriate use of antibiotics by developing and implementing the National Action Plan (NAP) on AMR.…”
Section: Introductionmentioning
confidence: 99%